Characterisation of a phantom for multiwavelength quantitative photoacoustic imaging. (10th June 2016) - Fonseca, M; Zeqiri, B; Beard, P C; Cox, B T
Abstract: Quantitative photoacoustic imaging (qPAI) has the potential to provide high- resolution in vivo images of chromophore concentration, which may be indicative of tissue function and pathology. Many strategies have been proposed recently for extracting quantitative information, but many have not been experimentally verified. Experimental phantom-based validation studies can be used to test the robustness and accuracy of such algorithms in order to ensure reliable in vivo application is possible. The phantoms used in such studies must have well-characterised optical and acoustic properties similar to tissue, and be versatile and stable. Polyvinyl chloride plastisol (PVCP) has been suggested as a phantom for quality control and system evaluation. By characterising its multiwavelength optical properties, broadband acoustic properties and thermoelastic behaviour, this paper examines its potential as a phantom for qPAI studies too. PVCP's acoustic properties were assessed for various formulations, as well as its intrinsic optical absorption, and scattering with added TiO2, over a range of wavelengths from 400-2000 nm. To change the absorption coefficient, pigment-based chromophores that are stable during the phantom fabrication process, were used. These yielded unique spectra analogous to tissue chromophores and linear with concentration. At the high peak powers typically used in photoacoustic imaging, nonlinear optical absorption was observed. The Grüneisen parameter was measured to be Γ   =  1.01  ±  0.05, larger than typically found in tissue, though useful for increased PA signal. Single and multiwavelength 3D PA imaging of various fabricated PVCP phantoms were demonstrated.